Peran manajemen strategis dalam pengembangan produk syariah yang disesuaikan dengan tren milenial - Najihah, Wilda ’Ainun (Maliki Interdisciplinary Journal, 2024)
In the context of intensifying global competition, Islamic financial institutions must adapt to maintain a competitive advantage and meet the expectations of young customers who prioritize technology and fast service. Using a qualitative approach, this study collected data from relevant literature, including articles and journals, to analyze how Islamic banks can implement effective strategies in product development. The results show that strategic management plays an important role in formulating and implementing strategies that not only focus on profitability, but also compliance with sharia principles. Islamic product development should involve all departments within the bank and consider factors such as quality, resource reliability, and digital marketing. In this way, Islamic banks can increase the appeal of their products among millennials who are the first generation to utilize technology. Millennials have a unique agenda regarding financial services, including payment transparency and social security. Therefore, Islamic banks’ product development strategies should be tailored to their needs and desires. Islamic banks that are able to offer products and services that meet the expectations of this generation will have great potential to attract and retain customers in the long run. Digital marketing is also important to attract the millennial generation. The use of digital platforms such as social media and mobile applications can increase the effectiveness of marketing campaigns and expand the benefits of sharia. By utilizing digital technology, Islamic banks can reach customers more effectively. Finally, this study concludes that effective strategic management in Islamic product development will play an important role in the growth of the Islamic finance industry. By changing its strategy to meet the needs of the millennial generation, Islamic banks can not only increase customer loyalty, but also contribute to the overall development of the Islamic economy. The purpose of this study is to explore the role of strategic management in developing Islamic products tailored to the needs of the millennial generation.